The Meaning of Qawwam in Q.S. An-Nisa: 34 (A Comparative Study of the Interpretations of Ibn Kathir and Al-Maraghi) - Syahroni, Asma; Nurrohim, Ahmad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Abstract The concept of qawwam in Q.S. An-Nisa: 34 is one of the topics that is widely discussed in the study of Qur'an interpretation, especially related to the relationship between husband and wife in the household. This verse is often used as a reference in understanding the husband's responsibility and leadership in the family, which is considered an important foundation in maintaining household harmony. This study aims to analyze the meaning of qawwam through a comparative study between Ibn Katsir's classical interpretation and Al-Maraghi's contemporary interpretation. Ibn Katsir used the tafsir bil-ma'tsur approach with an emphasis on narration sourced from the Prophet Muhammad PBUH, the companions, and the tabi'in. On the other hand, Al-Maraghi applies the method of tafsir bil-ra'yi with the style of adabi ijtima'i, which further highlights the relevance of Islamic values in modern social life. This study uses a qualitative method with a library research approach, where primary and secondary data from both interpretations are analyzed in depth. This analysis aims to identify the differences in methodology, social context, and interpretation of the two mufasirs on the concept of qawwam. The results of the study show that this difference in understanding is not only influenced by the interpretation method used, but also by the challenges and needs of each mufasir's era. Thus, this study makes a significant contribution to enriching the treasures of comparative interpretation while highlighting the relevance of the concept of qawwam in Muslim families in the modern era. Keywords: Qawwam, Ibnu Katsir, Al-Maraghi, Comparative Abstrak Konsep qawwam dalam Q.S. An-Nisa: 34 menjadi salah satu topik yang banyak dibahas dalam kajian tafsir Al-Qur'an, khususnya terkait hubungan suami istri dalam rumah tangga. Ayat ini sering dijadikan rujukan dalam memahami tanggung jawab dan kepemimpinan suami dalam keluarga, yang dianggap sebagai landasan penting dalam menjaga harmoni rumah tangga. Penelitian ini bertujuan untuk menganalisis makna qawwam melalui studi komparatif antara penafsiran klasik Ibnu Katsir dan tafsir kontemporer Al-Maraghi. Ibnu Katsir menggunakan pendekatan tafsir bil-ma’tsur dengan penekanan pada riwayat yang bersumber dari Nabi Muhammad SAW, para sahabat, dan tabi'in. Di sisi lain, Al-Maraghi menerapkan metode tafsir bil-ra’yi dengan corak adabi ijtima’i, yang lebih menyoroti relevansi nilai-nilai Islam dalam kehidupan sosial modern. Penelitian ini menggunakan metode kualitatif dengan pendekatan library research, di mana data primer dan sekunder dari kedua tafsir dianalisis secara mendalam. Analisis ini bertujuan untuk mengidentifikasi perbedaan metodologi, konteks sosial, dan interpretasi kedua mufasir terhadap konsep qawwam. Hasil penelitian menunjukkan bahwa perbedaan pemahaman ini tidak hanya dipengaruhi oleh metode tafsir yang digunakan, tetapi juga oleh tantangan dan kebutuhan zaman masing-masing mufasir. Dengan demikian, penelitian ini memberikan kontribusi signifikan dalam memperkaya khazanah tafsir komparatif sekaligus menyoroti relevansi konsep qawwam dalam keluarga Muslim di era modern. Kata kunci: Qawwam, Ibnu Katsir, Al-Maraghi, Komparatif